Varied diet and opportunistic foraging in the Ethiopian Bush-crow Zavattariornis stresemanni, an Endangered generalist. (2nd January 2018) - Jones, Samuel EI; Bladon, Andrew J; Collar, Nigel J; Dadacha, Galgalo; Denge, Jarso; Donald, Paul F
Abstract : The Ethiopian Bush-crow Zavattariornis stresemanni is an endangered, co-operatively breeding southern Ethiopian endemic with a remarkably restricted range (c. 6 000 km 2 ). The species' range was recently found to be almost perfectly predicted by an envelope of cooler, drier and more seasonal climate than surrounding areas, but the proximate determinants of this range restriction remain unclear. We assessed whether specialisation in diet or foraging may restrict the range of the species by conducting foraging watches to determine prey composition, augmented by observations of opportunistic foraging techniques, and by comparing our results to previously published information on diet. Prey composition comprised a range of arthropods, such as insect larvae (62.7%), beetles (Coleoptera) (15.6%), and grasshoppers and crickets (Orthoptera) (11.8%). Prey was primarily obtained by pecks above ground (74.2%) but also frequently dug up (23.8%). Prey capture was most successful during pecks and we also found chicks were preferentially fed larger prey items over smaller ones by adults. We documented opportunistic behaviours such as nest-raiding and ox-pecking. Diet and foraging are varied and unspecialised, and therefore do not appear to explain the restricted range of the Ethiopian Bush-crow.